Parents' views about factors facilitating their involvement in the oral early intervention services provided for their children with hearing loss in Kuwait. (January 2020) - Alduhaim, Alyaa; Purcell, Alison; Cumming, Steven; Doble, Maree
Abstract: Objectives: Developed countries (such as the Unites States of America, the United Kingdom, and Australia) provide high-quality services to children with hearing loss and their parents, including universal newborn hearing screening, early fitting of hearing devices and access to high quality early, aural intervention. In contrast, many developing countries lack the resources to provide these services. Research evidence suggests that one way to compensate for delays in identification and rehabilitation for children with hearing loss is to involve the family in the early intervention process. However, evidence is deficient around the facilitation of parental involvement in early intervention for families from developing countries. The aim of this study was to investigate the perception of parents from a developing country who have a child with hearing loss to discover the factors that may influence their involvement in early intervention, identify facilitators/barriers for their involvement, and identify the specific needs of involved parents. Method: A qualitative collective case study methodology was used in the form of semi-structured interviews with twenty-one participants. Results: Two global themes emerged. Firstly, factors influencing parental involvement. This included five subthemes: better communication as the key to building rapport and providing support; disappointment with the service; physical and human resources make a difference; consideration of life beyond the habilitation sessions; and my child matters the most. The second global theme-parental needs-included four subthemes: building trust; ensuring generalization; improving child outcomes; and managing needs of parents versus services. All the discussed themes are supported by quotations from the interviews. Conclusion: The findings suggest that parents of children with hearing loss in developing countries perceive the services provided for their children to be disjointed and not well coordinated. Based on the parent perceptions a set of guidelines that provide a scaffold for service providers working with children with hearing loss in developing countries is outlined. The guidelines are designed to assist services for children with hearing loss in developing countries improve the delivery of their services and increase family involvement, which in turn; will assist in improving their child and family related outcomes.